(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In order to reduce the population’s need for food and rational use of water resources in the conditions of typical irrigated gray soils Tashkent region, the sprinkling irrigation method was used for soybean crops "Nafis" and cauliflower "Raskot", while taking into account the volumetric mass of the soil, soil porosity, soil permeability. This is explained by the fact that the timing of irrigation, given to crops, irrigation rates, seasonal irrigation rates, the impact on growth, the development and productivity of plants are described